The Effect of Industrial Work Performance Practice and Performance Automotive Electrical Prakti entrepreneurial n Against Interests Automotive Mechanics Class XII Smk Diponegoro Depok Sleman - Arif Mustofa; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2013)
The purpose of this study was to determine (1) the influence of the industrial working practices achievement entrepreneurial interests, (2) the effect of automotive electrical practice achievement against entrepreneurial interests, and (3) influence of achievement and accomplishment industry work practices automotive electrical practices to entrepreneurial interest Automotive Mechanics XII class students of SMK Diponegoro Depok Sleman school year 2012/2013. Â The results showed that the test results of the partial correlation between achievements of industry working practices (X1) to entrepreneurial interest (Y) by controlling X2 correlation coefficient rx1-y = 0.471 and the partial correlation between the performance automotive electrical practices (X2) on entrepreneurial interest (Y) with X1 controlling fv values obtained correlation coefficient r = 0.259. Value of the determinant coefficient (R Â²) between X1, X2 x2-y with Y for 0.451, means the magnitude of the effect between X1 and X2 with Y is equal to 45.1%. Achievement industry work practices contribute effectively amounted to 22.32% of the interest in self-employment and achievements of automotive electrical practices provide effective contribution of 22.83% of the interest in entrepreneurship. Achievement industry work practices contributed to the relative amounting to 29.82% of the interest in entrepreneurship and achievement automotive electrical practices relative contribution of 70.18% to the entrepreneurial interests. Thus, achievement of industry work practices and achievements automotive electrical practices influence in fostering student interest in entrepreneurship.